2021
DOI: 10.1097/01.asw.0000767368.20398.14
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Surgical Site Infection following Emergency Cesarean Section: A Retrospective Case-Control Study

Abstract: Objective: To assess the incidence, risk and associated factors that contribute to an acquired Surgical Site Infection (SSI) in emergency Caesarean Section (CS).Design: Retrospective case-control study.Setting: An acute District General Hospital in England.Participants: 206 patients (101 SSI patients and 105 non-SSI patients) who had emergency CS between January-December 2017.Methods: Grade of surgeon, smoking status, pre-operative vaginal swab status (positive or negative), diabetes status, age, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…BMI was strongly associated with SSIs due to poor prescription techniques that exclude patients’ BMI, longer incision time, and slow transit of antibiotics due to thick adipose tissue that result in impaired wound healing and decreased immunity. This view on BMI has been supported by Ousley et al [ 15 ]. According to Chu et al [ 27 ], younger age in women is associated with an increased risk for SSIs due to underdeveloped immunity to fight infections.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…BMI was strongly associated with SSIs due to poor prescription techniques that exclude patients’ BMI, longer incision time, and slow transit of antibiotics due to thick adipose tissue that result in impaired wound healing and decreased immunity. This view on BMI has been supported by Ousley et al [ 15 ]. According to Chu et al [ 27 ], younger age in women is associated with an increased risk for SSIs due to underdeveloped immunity to fight infections.…”
Section: Discussionsupporting
confidence: 53%
“…This systematic review identified 5 cohort studies [ 16 - 20 ], 3 case-control studies [ 13 - 15 ], and 1 cross-sectional study [ 21 ]. After critical appraisal, 5 cohort studies [ 16 - 20 ] and 1 case-control study [ 13 ] were included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The pain in excess-weight patients was stronger on the fourth post-surgical day, and their CRP levels were higher. In other studies, obese patients developed septic postpartum complications more frequently [ 29 , 30 ], which could explain the presence of more severe pain and higher levels of CRP. However, in this study, obese patients more frequently developed septic complications, but the difference is not statistically significant, probably due to the small study population.…”
Section: Discussionmentioning
confidence: 96%